Surgery due to Inflammatory Bowel Disease During Pregnancy: Mothers and Offspring Outcomes From an ECCO Confer Multicentre Case Series [Scar Study]. (4th April 2022) - Chaparro, María; Kunovský, Lumír; Aguas, Mariam; Livne, Moran; Rivière, Pauline; Bar-Gil Shitrit, Ariella; Myrelid, Pär; Arroyo, Maite; Barreiro-de Acosta, Manuel; Bautista, Michelle; Biancone, Livia; Biron, Irit Avni; et al.
Abstract: Aims: i] To evaluate the evolution of pregnancies and offspring after inflammatory bowel disease [IBD] surgery during pregnancy; and ii] to describe the indications, the surgical techniques, and the frequency of caesarean section concomitant with surgery. Methods: Patients operated on due to IBD during pregnancy after 1998 were included. Participating clinicians were asked to review their databases to identify cases. Data on patients' demographics, IBD characteristics, medical treatments, IBD activity, pregnancy outcomes, surgery, delivery, and foetal and maternal outcomes, were recorded. Results: In all, 44 IBD patients were included, of whom 75% had Crohn's disease; 18% of the surgeries were performed in the first trimester, 55% in the second, and 27% in the third trimester. One patient had complications during surgery, and 27% had postsurgical complications. No patient died. Of deliveries, 70% were carried out by caesarean section. There were 40 newborns alive. There were four miscarriages/stillbirths [one in the first, two in the second, and one in the third trimester]; two occurred during surgery, and another two occurred 2 weeks after surgery; 14% of the surgeries during the second trimester and 64% of those in the third trimester ended up with a simultaneous caesarean section or vaginal delivery. Of the 40 newborns, 61% were premature and 47% had low birth weight; 42% of newborns needed hospitalisation [25% in the intensive care unit]. Conclusions: IBD surgery during pregnancy remains an extremely serious situation. Therefore, surgical management should be performed in a multidisciplinary team, involving gastroenterologists, colorectal surgeons, obstetricians, and neonatal specialists.